Dual-Frequency Sensor for Thick Rind Fruit Quality Assessment - Kittiyanpunya, Chainarong; Phongcharoenpanich, Chuwong; Krairiksh, Monai (My University, 2020)
This article proposes a novel multibeam dual-frequency sensor system to assess the quality of thick rind fruits based on phase difference between lower- and higher-frequency reflection coefficients ( Φ {12} ). The proposed sensor system consists of five dual-band antennas and a customized circuit that approximates lower- and higher-frequency phase difference. The main components of the customized circuit are down-conversion mixers and a phase detector module. For comparison, simulations were initially carried out using single- (1 GHz) and dual-frequency (1 GHz/2.3 GHz) sensor systems, and results indicated lower accuracy in classification of thick rind fruits of the single-frequency scheme. As a result, a dual-frequency sensor prototype was fabricated and experimented with normal and granulated plastic pomelo models and real pomelo fruits. The experimental results revealed that the average Φ{12} of the normal and granulated pomelos are almost identical, while the standard deviation (SD) of Φ 12 of the granulated pomelo is significantly larger than the normal pomelo. SD is thus used as the determinant of pomelo quality. The multibeam 1-GHz/2.3-GHz dual-frequency sensor system efficiently differentiates between normal and granulated pomelo fruits. As such, the proposed sensor system is operationally appropriate for quality control of thick rind fruits.
Keywords: Dielectric constant variation; dual-band antenna; fruit classification; microwave sensor